Introductory Statistics - Illowsky, Barbara; Dean, Susan; Birmajer, Daniel; Blount, Bryan; Boyd, Sheri; Einsohn, Matthew; Helmreich, James; Kenyon, Lynette; Lee, Sheldon; Taub, Jeff (Open textbook library., 2024)
Introductory Statistics 2e provides an engaging, practical, and thorough overview of the core concepts and skills taught in most one-semester statistics courses. The text focuses on diverse applications from a variety of fields and societal contexts, including business, healthcare, sciences, sociology, political science, computing, and several others. The material supports students with conceptual narratives, detailed step-by-step examples, and a wealth of illustrations, as well as collaborative exercises, technology integration problems, and statistics labs. The text assumes some knowledge of intermediate algebra, and includes thousands of problems and exercises that offer instructors and students ample opportunity to explore and reinforce useful statistical skills.